1995
DOI: 10.1074/jbc.270.41.24306
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Microtubule-associated Protein Tau under Near-physiological Conditions

Abstract: Neurofibrillary tangles, which form in certain degenerating neurons in the brains of patients with Alzheimer's disease, are amassed from filaments having a straight or paired helical morphology. Solubilization of these filaments reveals that they are composed of the microtubule-associated protein tau. It has not previously been shown, however, that tau will assemble to form filaments of similar morphology under conditions representative of the intracellular environment. We have succeeded in forming such filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 59 publications
3
58
0
Order By: Relevance
“…In fact, the solubility of Tau in vitro is millimolar, much higher than its concentration in cells ( micromolar), which explains in part why it has taken a long time to discover assembly conditions in vitro ( Fig. 3; Wille et al 1992;Crowther et al 1994;Wilson and Binder 1995). However, two factors contribute to pushing Tau toward aggregation.…”
Section: Structure Of Tau Fibers (Phfs)mentioning
confidence: 99%
“…In fact, the solubility of Tau in vitro is millimolar, much higher than its concentration in cells ( micromolar), which explains in part why it has taken a long time to discover assembly conditions in vitro ( Fig. 3; Wille et al 1992;Crowther et al 1994;Wilson and Binder 1995). However, two factors contribute to pushing Tau toward aggregation.…”
Section: Structure Of Tau Fibers (Phfs)mentioning
confidence: 99%
“…Some author reported that assembly of microtubule-associated protein tau into Alzheimer-like filaments could be induced by sulphated glycosaminoglycans, especially by heparin [1][2][3][4][5][6][7][8][9][10][11]. We compared the kinetics in the fluorescence formation and in light scattering while tau was incubated with and without heparin ( Table 1).…”
Section: The Fluorescence At 333 Nm In6ol6ing Tau's Polymerizationmentioning
confidence: 99%
“…Filaments with a straight or paired helical morphology are the major components of the neurofibrillary tangles that form a defining neuropathological characteristic of Alzheimer's disease [1,2]. Solubilization of these filaments reveals that they are composed of the microtubule-associated protein tau [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under some conditions, tau aggregates and forms straight or paired helical filaments (PHFs) that are the major components of NFTS, a totally inactivated form in neuropathological characteristic of AD (26)(27)(28). In this lab, it has been found that tau interacts with d-glyceraldehyde-3-phosphate dehydrogenase (GAPDH), in a chaperone-like manner (29).…”
Section: Introductionmentioning
confidence: 99%